Comanche Song - Shefelman, Janice Jordan, 1930-; Shefelman, Tom (Austin, Tex. : Eakin Press, 2000)
A young Comanche boy experiences his tribe's conflicts with the Tejanos in 1840s Texas.
Map of Tsena's journeys on lining papers.
Keywords: Comanche Indians -- Fiction; Comanche Indians -- Fiction; Indians of North America -- Fiction -- Texas; Texas -- Fiction